HOW TO TEACH STUDENTS USING POSITIVE WORDS IN UTTERANCE (SPEECH ACTS-APPLICATION) - Kokok Dj Purwanto; Supeno Supeno (Jurnal Scientia, 2022)
Words have the power and a huge impact to affect others both in positive and negative terms. Words can hurt or heal, and even words can also create or destroy, it depends on how people deliver words in utterance or a speech act to others. Words in utterance or a speech act are usually accompanied by gestures and physical activity ( kinesthetic- red ) in conveying the intentions and purposes. One word can end a fight, one look can save a relationship, one smile can start a relationship and one person can change your life. Therefore, people have to speak to the mind and appeal to the heart. This descriptive research tends to find out how words both in utterance and in a speech act can influence people’s moods, people’s opinions or even people’s minds about something or someone